Neonatal Out Come in High Risk Pregnancy (TAJ: Journal of Teachers Association, 2010)
A 12 months study was carried out on 226 pregnant high risk patients attending in Rajshahi Medical College Hospital from January 2008 to December 2008. The aim of the study was to identify various type of high risk pregnancies and to determine social and educational status as well as new born conditions of birth. Among the 226 recruited patients 69.5% came from rural area. Among the 69.5% rural high risk patients 63.69% were illiterate. Live born baby in this study was 95.13%. In our study neonatal out come was excellent. Excellent out come was attributed to early diagnosis of high risk pregnancy and suitable intervention both by Obstetrician and Paediatrician. DOI: 10.3329/taj.v22i1.5016 TAJ 2009; 22(1): 26-29